PENERAPAN MODEL PEMBELAJARAN STUDENT FACILITATOR AND EXPLAINING BERBANTUAN MIND MAPPING UNTUK MENINGKATKAN KEMAMPUAN KOMUNIKASI DAN HASIL BELAJAR MATERI JENIS USAHA EKONOMI KELAS V SD BABALAN - Wahyuningtiyas, Erni; Sulianto, Joko; Saputra, Henry Januar (Universitas PGRI Semarang, 2022)
The results of observations at SD N Babalan show that the students' learning outcomes and communication skills are low. The learning models and media used by teachers are less varied, causing learning that takes place to seem boring. Therefore, in this study the researchers applied learning with the SFAE model combined with mind mapping which helps students to understand the material on the types of economic enterprises. This study aims to improve learning outcomes and students' oral communication skills in the learning process through a student facilitator and explaining learning model assisted by mind mapping.The results showed that the application of the student facilitator and explaining learning model assisted by mind mapping on the material of the type of economic business in class V SD N Babalan can improve student communication skills followed by an increase in student learning outcomes. This can affect student learning outcomes which have increased from 59 students' average score before being given action to 73 in cycle I and increased again in cycle II with an average of 83 after being given the action.Keywords: Learning Outcomes, Communication Skill, Student Facilitator and Explaining, Mind Mapping